Personal construct methodology - Caputi, Peter (Malden, MA : Wiley, 2012)
'Written by an international team of experts, this collection provides a comprehensive account of established and emerging methods of collecting and analysing data within the framework of personal construct theory. Covers methods such as content analysis scales, repertory grid methodology, narrative assessments and drawings, the laddering and ABC techniques, and discusses how and why they are used Explores both qualitative and quantitative methods, as well as methods used in clinical and counselling settings Includes 13 contributions from leading international scholars'--
'This book provides easy to follow descriptions and examples of applications in clinical and non-clinical settings and explains how and why certain methods are used and in which contexts they are likely to have the most success'--
Includes bibliographical references and index.
Keywords: Personal construct theory; Social sciences -- Statistical methods